Considering frictional slippage at saddle-cable interface in seismic behavior of a suspension bridge. Issue 5 (April 2021) - Zhao, Canhui; Duan, Jiahong; Zeng, Xianzhi; Deng, Kailai; Guo, Jia; Yang, Shaojun; Wen, Qiang
Long-span suspension bridges are widely used in deep valleys, which face severe seismic risk. However, the potential saddle-cable frictional slippage under earthquake excitation as well as its influence on the seismic response of the whole suspension bridge has not yet been investigated. To investigate the effect of frictional slippage at the saddle-cable interface, this paper developed a nonlinear numerical model that considers the saddle-cable slippage. Another contrasting model with a non-slipping saddle-cable interface was used for quantitative comparison. Nonlinear dynamic analyses were conducted using these two models. The saddle-cable interfacial response indicated the realization of the frictional slippage at the saddle-cable interface under the maximum considered earthquake. The overall damage patterns, critical sectional performance, main girder drift, and energy dissipation were discussed in detail. Under the design based and maximum considered intensities, the saddle-cable slippage was seldom observed. The visible frictional slippage was encountered only at ultimate safety earthquake, which could be helpful to limit the transferred load, protect the pylon from yielding, and dissipate approximately 14% of the input seismic energy. While the slippage could not evidently affect the overall deformation pattern of the suspension bridge, as well as the response of bearings and central buckles.